RECODIFICATION OF CORE CRIMES IN SPECIAL CRIMINAL ACTS WITHIN LAW NUMBER 1 OF 2023 CONCERNING THE PENAL CODE - Euis Rachmawati Abdullah; Dwi Nur Fauziah Ahmad (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research focuses on investigating the Recodification of Core Crimes in Special Criminal Acts within Law Number 1 of 2023 concerning the Penal Code. The study is motivated by the enactment of Law Number 1 of 2023 concerning the Penal Code (National Penal Code) through the process of criminal law recodification, which has sparked controversy among institutions and law enforcement officials. This controversy arises due to the inclusion of core crimes from special criminal acts in the National Penal Code. The issues addressed in this research are the regulation of core crimes from special criminal acts within the National Penal Code and the implications of this regulation for other criminal laws outside the Penal Code, using normative research methods to uncover the truth behind two key issues. The research findings indicate that the inclusion of core crimes from special criminal acts in the National Penal Code will not create ambiguity with existing special criminal laws outside the Penal Code nor complicate the law enforcement process. The inclusion of core crimes from special criminal acts in the Penal Code aims to provide a bridging mechanism so that if a new offense or development of an offense arises, there will still be a reference to the National Penal Code, ensuring that the fundamental principles remain aligned with the National Penal Code, as most current regulations on special criminal acts deviate from general principles or their enforcement.